Microvascular and macrovascular complications of type 2 diabetes mellitus: Exome wide association analyses - Mansour, Afnan; Mousa, Mira; Abdelmannan, Dima; Tay, Guan; Hassoun, Ahmed; Alsafar, Habiba (Frontiers in Endocrinology, 2023)
T2DM is a chronic, metabolic disorder in which concomitant insulin resistance and β-cell impairment lead to hyperglycemia, influenced by genetic and environmental factors. T2DM is associated to long-term complications that have contributed to the burden of morbidity and mortality worldwide. The objective of this manuscript is to conduct an Exome-Wide Association Study on T2DM Emirati individuals to improve our understanding on diabetes-related complications to improve early diagnostic methods and treatment strategies. This cross-sectional study recruited 310 Emirati participants that were stratified according to their medically diagnosed diabetes-related complications: diabetic retinopathy, diabetic neuropathy, diabetic nephropathy, and cardiovascular complications. The analysis revealed the associations of various genes with each complication category: 1) diabetic retinopathy was associated to SHANK3 gene (SNP rs9616915; p=5.18 x10-4), ZSCAN5A gene (SNP rs7252603; p=7.55 x10-4), and DCP1B gene in locus 12p13.33 (SNPs rs715146, rs1044950, rs113147414, rs34730825; p=7.62 x10-4); 2) diabetic neuropathy was associated to ADH4 gene (SNP rs4148883; p=1.23 x10-4), SLC11A1 gene (SNP rs17235409; p=1.85 x10-4), and MATN4 gene (SNP rs2072788; p=2.68 x10-4); 3) diabetic nephropathy was associated to PPP1R3A gene (SNP rs1799999; p=1.91 x10-4), ZNF136 gene (SNP rs140861589; p=2.80 x10-4), and HSPA12B gene (SNP rs6076550; p=2.86 x10-4); and 4) cardiovascular complications was associated to PCNT gene (SNPs rs7279204, rs6518289, rs2839227, rs2839223; p=2.18 x10-4 ,3.04 x10-4,4.51 x10-4,5.22 x10-4 respectively), SEPT14 gene (SNP rs146350220; p=2.77 x10-4), and WDR73 gene (SNP rs72750868; p=4.47 x10-4). We have identified susceptibility loci associated with each category of T2DM-related complications in the Emirati population. Given that only 16% of the markers from the Illumina’s Infinium Exome chip passed quality control assessment, this demonstrates that multiple variants were, either, monomorphic in the Arab population or were not genotyped due to the use of a Euro-centric EWAS array that limits the possibility of including targeted ethnic-specific SNPs. Our results suggest the alarming possibility that lack of representation in reference panels could inhibit discovery of functionally important loci associated to T2DM complications. Further effort must be conducted to improve the representation of diverse populations in genotyping and sequencing studies.